Erythropoietin Derived Peptide Improved Endoplasmic Reticulum Stress and Ischemia-Reperfusion Related Cellular and Renal Injury - Zhang, Yufang; Wang, Qian; Liu, Aifen; Wu, Yuanyuan; Liu, Feng; Wang, Hui; Zhu, Tongyu; Fan, Yaping; Yang, Bin (Frontiers in Medicine, 2020)
Ischemia-reperfusion (IR) injury often affects transplant and native kidneys alike. IR injury is one of the main causes of acute kidney injury (AKI) and further associated with the progression of chronic kidney disease. Our previous study revealed the renoprotection of erythropoietin derived cyclic helixB surface peptide (CHBP) against IR injury. However, the precise role and underlying mechanism of endoplasmic reticulum stress (ERS) in the injury and the renoprotection induced by IR or CHBP respectively have not been fully defined. This study using mouse kidney epithelial cells (TCMK-1) revealed that the level of CHOP (a key marker of ERS), PERK and JNK (regulators of CHOP) was gradually increased by the prolonged time of hydrogen peroxide (H2O2) stimulation. In addition, CHOP mRNA and protein were significantly reduced by small interfering RNA (siRNA) target CHOP, as were apoptotic and inflammatory mediator caspase-3 and HMGB-1, and early apoptosis. Furthermore, CHOP mRNA was correlated positively with PERK protein, active caspase-3, HMGB-1 and apoptosis, but negatively with cell viability in vitro, while CHOP protein was also correlated positively with the level of tubulointerstitial damage and active caspase-3 protein in vivo. Finally, CHBP improved the viability of TCMK-1 cells subjected to H2O2 stimulation time-dependently, with reduced level of CHOP mRNA. CHBP also inhibited the increase of CHOP protein, not only in TCMK-1 cells, but also in the IR injury kidneys at 2 weeks. Moreover, CHBP reduced the expression of PERK mRNA and protein, JNK and HMGB-1 protein, as well as early and later apoptosis. In addition, raised CHOP at 12 h post IR injury might be an early time window for intervention. In conclusion, the differential role of ERS and CHBP in IRrelated injury was proved in mouse TCMK-1 cells and kidneys, in which the mechanistic signaling pathway was associated with CHOP/PERK/JNK, HMGB-1/caspase-3, and apoptosis. CHOP might be a potential biomarker and CHBP might be therapeutic drug for IR-induced AKI.